Hydrogen Sulfide Relaxes Human Uterine Artery by Activating Smooth Muscle BKCa Channels: A Recent Study - Yan Li; Jin Bai; Yi-hua Yang; Naoto Hoshi; Dong-bao Chen (New Horizons in Medicine and Medical Research Vol. 10, 2022)
Background: The opening of large conductance calcium-activated and voltage-dependent potassium (BKCa) channels causes vasodilation by hyperpolarizing smooth muscle (SM) plasma membranes, which is a crucial mechanism for mediating uterine artery (UA) dilatation during pregnancy. H2S has recently been identified as a new UA vasodilator; nevertheless, the mechanisms behind H2S-induced UA dilatation are unknown. Aims: To explore the mechanisms by which H2S relaxes human UA. Methods: Main uterine arteries were collected from pregnant women at caesarean hysterectomy. Primary smooth muscle cells were isolated and cultured for electrophysiology studies. Protein and mRNA expressions of BKCa channels were measured by immunofluorescence microscopy and Western blot and RT-PCR. Freshly prepared uterine artery rings were used for organ bath studies. Results: In vitro, multiple BKCa subunits were discovered in human UA and hUASMC, with high \(β\)1and \(γ\)1proteins localized in SM cells. Specific BKCa blockers iberiotoxin (IBTX) or tetraethylammonium significantly inhibited baseline outward currents. H2S increased BKCa currents and channel open probability in a dose-dependent manner. Ca2+ blocker nifedipine (5 \(μ\) M) or a chelator ethylene glycol-bis ( \(β\) -aminoethyl ether)- \( N.N., N’, N’ \)-tetraacetic acid (EGTA, 5 mM) did not alter H2S-potentiated BKCa currents and open probability. NaHS dose-dependently relaxed phenylephrine pre-constricted freshly prepared human UA rings and this was inhibited by IBTX. Conclusions: H2S stimulates human UA relaxation at least partially via activating SM BKCa channels independent of extracellular Ca2+.